The Design of Corporate Debt Structure and Bankruptcy - von Thadden, Ernst-Ludwig; Berglöf, Erik; Roland, Gérard (Review of Financial Studies, 2010)
This article integrates the problem of designing corporate bankruptcy rules into a theory of optimal debt structure. We show that, in an optimal contracting framework with imperfect renegotiation, having multiple creditors increases a firm’s debt capacity while increasing its incentives to default strategically. The optimal debt contract gives creditors claims that are jointly inconsistent in case of default. Bankruptcy rules are therefore a necessary part of the overall financing contract, to make claims consistent and to prevent a value-reducing run for the assets of the firm. We characterize these rules, with predictions about the allocation of security rights, the right to trigger bankruptcy, and the symmetry of treatment of creditors in default.